Procedure for Transfer of Trademark Rights as a Debt Settlement Measure in Corporate Bankruptcy Proceedings : Case Study of PT. Nyonya Meneer's Bankruptcy - Fachri Hafizd Selian; Muthia Sakti; Iwan Erar Joesoef (Green Social: International Journal of Law and Civil Affairs, 2025)
This study examines the transfer of trademark rights as a means of debt settlement in corporate bankruptcy proceedings, using the bankruptcy case of PT Nyonya Meneer as a case study. The main issue addressed is how trademarks, as intangible intellectual property with high economic value, can be used as debt settlement assets during bankruptcy. This research employs a normative legal method with statutory and conceptual approaches, supported by a review of relevant court decisions. The analysis focuses on the relationship between the provisions of Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations and Law No. 20 of 2016 on Trademarks. Trademarks may be transferred or sold to fulfill the debtor's obligations. Theoretical foundations include the Creditors’ Bargain Theory (Thomas H. Jackson) and the principle of wealth maximization (Richard A. Posner), emphasizing collective settlement and asset value optimization. The findings reveal that trademark transfer in bankruptcy is not explicitly regulated, creating a legal gap that affects the effectiveness of debt settlement and the protection of creditors’ rights. In the PT Nyonya Meneer case, the trademark despite its potential as a debt settlement instrument was not utilized optimally. Therefore, direct transfer of trademarks to creditors as a form of debt payment can be seen as an alternative solution, provided it is conducted under the principles of justice, legal certainty, and efficiency. This study recommends further regulation on the management and transfer of intellectual property within the bankruptcy regime to address the challenges of modern business practices.